Nucleoside analogues in treatment of liver cirrhosis as an outcome of chronic hepatitis B - I. G. Bakulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To estimate safety and efficacy of prescription of nucleoside analogues the patient with liver cirrhosis in an outcome of chronic hepatitis B.Original positions of the report. Rates of progression of persistent HBV infection to liver cirrhosis stage depend on several factors – spectrum of viral markers, immune status of the patient, his/her age, gender, genetic predisposition, etc. Lamivudine has capacity for prolonged and persistent block of HBV replication. Its antiviral effect limited basically by development of drug resistance of a virus as a result of mutant strains development. Terms of lamivudine treatment for patients with liver cirrhosis should be no less than 22 months, and clearance HBV DNA is achieved in 93,9 % of patients. Sustained virologic response (it was assessed in 4 years after termination of treatment course) is estimated as 39%. Entecavir has higher (in comparison to lamivudine) efficacy in relation of supression of HBV virus replication and achievement of non-detectable level of viral load. The biochemical response in the group of cirrhotic patients at entecavir application is obtained at 63% НВеAg-positive and at 78% of НВеAg-negative patients. The virological response (supression of HBV replication) at entecavir treatment was: at НВеAg positive – 91%, at НВеAg-negative – 96%. The rate of histological response in the group treated by entecavir was significantly higher, than in group treated by lamivudine: in НВеAg-positive – 80 and 64%, in НВеAg-negative – 75 and 60% respectively.Conclusion. At application of entecavir on a background of supression of viral replication the main strategic goal of antiviral therapy - regression of necroinflammatory changes in the liver at patients with HBV-viral cirrhosis is achieved.